The influence of Ta’awun and Infaq in sustaining affordable housing among lower income earners in Malaysia - Ahmad, Anisah; Sarif, Suhaimi Mhd (IKAZ ACIS UITM, 2019)
This study explores the influence of ta’awun (strategic cooperation and complementary) and infaq (judicious spending and savings) in sustaining the need for affordable housing among lower income earners in big cities of Malaysia. Affordable housing is no ending issue in the context of open market-economy. The study interviewed key stakeholders of affordable housing. Ta’awun and infaq are capable for sustaining the affordability of house buying into design of home, increasing combined income, gaining more respect, and integrated capability.